Land use change between 1997 and 2023 in Parque Regional Municipal Los Altos de San Miguel Totonicapán, Guatemala - Ixcotoyac-Cabrera, Priscila Isabel (2025)
This study was conducted in the Parque Regional Municipal Los Altos de San Miguel Totonicapán, Guatemala, with the aim of assessing land use changes from its establishment as a protected area in 1997 to 2023. Google Earth Engine and QGIS 3.34 were used, performing supervised classification on satellite images from 1997 (Landsat 5) and 2023 (Landsat 9), achieving accuracies of 97.62% for 1997 and 100% for 2023 using the random forest algorithm, with 1253 field observations associated with land uses, categorized into urbanized areas, agricultural lands, forests, and semi-natural environments. The results show a 22% increase in urban areas, a 25% decrease in agricultural lands, and a 4% increase in forests and semi-natural environments. The preservation and increase in forest cover is primarily attributed to the management and ancestral practices of the K'iche' Maya communities. Other abandoned agricultural areas have begun restoration processes, and the communities have conducted reforestation efforts to contribute to forest cover recovery. However, this recovery is carried out with a few species, which could affect the quality of the ecosystem services. Additionally, urban growth is linked to improved socioeconomic conditions, which have driven the demand for housing and infrastructure services. These findings highlight the need to promote initiatives to mitigate degradation and ensure the sustainability of the native forest.